6(3x-2)=3-2(4x+1)

Simple and best practice solution for 6(3x-2)=3-2(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-2)=3-2(4x+1) equation:


Simplifying
6(3x + -2) = 3 + -2(4x + 1)

Reorder the terms:
6(-2 + 3x) = 3 + -2(4x + 1)
(-2 * 6 + 3x * 6) = 3 + -2(4x + 1)
(-12 + 18x) = 3 + -2(4x + 1)

Reorder the terms:
-12 + 18x = 3 + -2(1 + 4x)
-12 + 18x = 3 + (1 * -2 + 4x * -2)
-12 + 18x = 3 + (-2 + -8x)

Combine like terms: 3 + -2 = 1
-12 + 18x = 1 + -8x

Solving
-12 + 18x = 1 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-12 + 18x + 8x = 1 + -8x + 8x

Combine like terms: 18x + 8x = 26x
-12 + 26x = 1 + -8x + 8x

Combine like terms: -8x + 8x = 0
-12 + 26x = 1 + 0
-12 + 26x = 1

Add '12' to each side of the equation.
-12 + 12 + 26x = 1 + 12

Combine like terms: -12 + 12 = 0
0 + 26x = 1 + 12
26x = 1 + 12

Combine like terms: 1 + 12 = 13
26x = 13

Divide each side by '26'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 | | -4x+14y=2 | | -6x+25=-3x+13 | | 3p-14=p | | 18=2t+8 | | -3x-3=-2x-2 | | x^2-88=-7 | | 0.09xX=123.42 | | 11x+21=6x+11 | | p/7=28 | | 15x+50=9x+32 | | 2(3x-4)=7(2x+5) | | 3-(x+2)=1 | | -r/3≤6 | | 28=p/7 | | -20x+24=-12x+16 | | -12x+63=-8x+39 | | -9x+69=-6x+45 | | t-22.4=34.8 | | -77=-9a-5 | | 11x-32=7x-20 | | X-4-5=0 |

Equations solver categories